Halal economy in the global markets: new source of investment and economic growth - Baharumshah, Ahmad Zubaidi (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
There are approximately 1.5 billion Muslims in the world and majority of the world’s Muslim population is located in the Asia-Pacific region. According to Global Islamic Economy Report in 2013, the global expenditure of Muslim consumers on food and lifestyle sector is being estimated to be 1.62 trillion US dollar in 2012 and is expected to increase by more than 53 by 2018. This has raised attention in many people’s minds recently as to what the Halal Economy refers to. Does it refer to the economies of the Organization of Islamic Cooperation (OIC)? Are the consumers of the Islamic economy (e.g. Islamic finance) limited only to Muslims? Does it refer to green, purity and non-pollution? Can this halal economy promote new investments and economic growth? The primary aim of this paper is to offer a global perspective of the halal economy. The paper looks at the definition of halal economy and five existing sectors, namely halal food, Islamic finance, clothing or fashion, halal tourism, and pharmaceutical and cosmetic sectors. In addition to that, the prospects of Malaysia’s major halal exported products and destinations are reviewed. Some challenges and opportunities will be highlighted in the last section.